2011
DOI: 10.1097/gim.0b013e318203cff2
|View full text |Cite
|
Sign up to set email alerts
|

Next generation massively parallel sequencing of targeted exomes to identify genetic mutations in primary ciliary dyskinesia: Implications for application to clinical testing

Abstract: PURPOSE Advances in genetic sequencing technology have the potential to enhance testing for genes associated with genetically heterogeneous clinical syndromes, such as primary ciliary dyskinesia (PCD). The objective of this study was to investigate the performance characteristics of exon-capture technology coupled with massively parallel sequencing for clinical diagnostic evaluation. METHODS We performed a pilot study of four individuals with a variety of previously identified PCD mutations. We designed a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 37 publications
1
56
0
Order By: Relevance
“…The prospect that the patient carries mutations in another PCD gene must also be considered with the DNAH11 mutation contributing to a multigenic defect in combination with one or more other PCD locus mutations. A recent report of a PCD patient with only a single frameshift mutation in DNAH11 was suggested to result from digenic inheritance with a DNAH2 (MIM# 603333) variant [Berg et al, 2011], although the authors indicate that further studies are required. However, these human data, combined with the evidence that mutations in the mouse homolog can be associated with static cilia, supports the hypothesis that DNAH11 mutations can cause static cilia, in addition to the previously described association with stiff vibrating/hyperfrequent cilia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prospect that the patient carries mutations in another PCD gene must also be considered with the DNAH11 mutation contributing to a multigenic defect in combination with one or more other PCD locus mutations. A recent report of a PCD patient with only a single frameshift mutation in DNAH11 was suggested to result from digenic inheritance with a DNAH2 (MIM# 603333) variant [Berg et al, 2011], although the authors indicate that further studies are required. However, these human data, combined with the evidence that mutations in the mouse homolog can be associated with static cilia, supports the hypothesis that DNAH11 mutations can cause static cilia, in addition to the previously described association with stiff vibrating/hyperfrequent cilia.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations causing truncation or frame shift (FS) are shown with a dotted line downstream of the mutation. From the N-terminus mutations are from the following studies c.855-1G>A [Pifferi et al, 2010]; p.Trp1382 * [Pifferi et al, 2010]; lrm3 mouse-50 amino acids missing [Ermakov et al, 2009]; p.Ser2176 * (this study); iv mouse [Supp et al, 1997]; p.Pro2598Leu (this study); p.His2712Arg [Pifferi et al, 2010];p.Arg2852 * [Bartoloni et al, 2002]; p.Arg2907 * (this study); p.Lys3038Thrfs * 13 [Berg et al, 2011]; p.Gly3428Arg [Pifferi et al, 2010]; p.Tyr4128 * [Schwabe et al, 2008]; p.4518 4523delinsQ [Schwabe et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For nNO validation studies at six (non-UNC) sites, PCD was confirmed by PCD-specific ciliary EM defects and, by the presence of biallelic mutations in PCD genes (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Informed consent was obtained at the University of North Carolina at Chapel Hill and collaborating institutions under the auspices of Committees on the Protection of the Rights of Human Subjects.…”
Section: Original Researchmentioning
confidence: 99%
“…A clinical implementation of genomics has to be scaled to the new reality of whole-genome analysis. 9 With the advent of next-generation sequencing technologies, the ability to quickly and relatively inexpensively learn the sequence of an individual's entire genome will soon be available to medical practitioners, patients, and consumers. 10,11 In this study of a large FALS family, we opted to apply whole-exome sequencing and, as a consequence, have successfully identified a novel mutation of the superoxide dismutase 1 (SOD1) gene.…”
Section: Introductionmentioning
confidence: 99%